2007
DOI: 10.1152/jn.01126.2006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Viscous Loads on Motor Planning

Abstract: Here we computationally investigate how encumbering the hand could alter predictions made by the minimum torque change (MTC) and minimum endpoint variance hypotheses (MEPV) of movement planning. After minutes of training, people have made arm trajectories in a robot-generated viscous force field that were similar to previous baseline trajectories without the force field. We simulate the human arm interacting with this viscous load. We found that the viscous forces clearly differentiated MTC and MEPV prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The minimum variance is equal to the minimum weighted sum of motor commands when signal-dependent noise is assumed. This notion was supported by the simulations of Thoroughman et al (2007), in which large overcompensation was predicted by both minimum torque change and minimum variance models in the force-field task. Because these models all minimize the sum of motor commands, the typical OFC problem that has motor costs is closely related to these two models.…”
Section: Discussionmentioning
confidence: 72%
“…The minimum variance is equal to the minimum weighted sum of motor commands when signal-dependent noise is assumed. This notion was supported by the simulations of Thoroughman et al (2007), in which large overcompensation was predicted by both minimum torque change and minimum variance models in the force-field task. Because these models all minimize the sum of motor commands, the typical OFC problem that has motor costs is closely related to these two models.…”
Section: Discussionmentioning
confidence: 72%
“…When the same perturbation is applied repetitively, these models generally predict an exponential learning curve toward complete adaptation, which has been observed in various motor adaptation studies. With block learning, subjects can produce forces that very well cancel force perturbations such as a velocity-dependent force field (Shadmehr and Mussa-Ivaldi 1994;Thoroughman et al 2007), position-dependent force field (Tong et al 2002), and altered inertial property of the limb (Krakauer et al 1999). They can also produce movements that cancel a visual perturbation such as a visuomotor rotation (Ghahramani and Wolpert 1997;Pine et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using reach adaptation in static environments have also shown that energy is not always the most important factor that drives the movement [ 26 29 ]. Kistemaker and co-workers [ 27 , 28 ] showed that subjects, after they successfully learnt to reach through a force field along an energetic optimal path, do not choose this path in trials where they were free to choose how to move through the force field.…”
Section: Discussionmentioning
confidence: 99%